Colonoscopy-Assisted Resolving of Intussusception in Children, a Report of 15 Cases - Iraj Shahramian (Shiraz University of Medical Sciences, 2020)
There are few reports on the therapeutic role of colonoscopy in correcting intussusception of childhood. In the present report, 15 children (14 boys and 1 girl) presented with acute intussusception and successfully treated by colonoscopy were presented. The patients were referred to the gastroenterology clinic of Ami-Al-Momenin Hospital, Zabol, Iran from 2015 to 2018. The mean age of the patients was 36.6±28.7 months. After stablishing the diagnosis, they underwent colonoscopic reduction of intussusception by an experienced gastroenterologist. Following 24 hours of the procedure, follow up sonography was performed. Overall, 6 recurrences were identified in 4 (26.7%) patients which were managed by a second colonoscopy. A second recurrence was detected in two patients who finally underwent surgical reduction. Regarding the role of colonoscopy in providing a visual and real-time setting, this can be used as either a primary option or an alternative to radiologic and surgical procedures of intussusception reduction in children.